2007
DOI: 10.1182/blood.v110.11.4553.4553
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Response in Relation to the Adherence to Treatment with Imatinib Mesylate: A Case Control Study.

Abstract: Introduction: The treatment of chronic myeloid leukemia (CML) suffered a dramatic change with the introduction of Imatinib mesylate. This drug has become the choice for first line treatment of CML. However, it has been shown that the effectiveness of the treatment requires a high compliance with the prescribed dose for a long period of time, and sub-dosing has been associated with a delay in achieving cytogenetic response and development of resistance. We conducted a prospective case-control study, in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Median/mean MPRs have been reported in other studies in the range of 0.64 and 0.96. 9,11,19,20 Thirty-one percent of patients in our study were found to have a MPR < 0.9. Past studies have reported 30% to 46% of patients to be non-adherent to their TKI regimen.…”
Section: Discussionmentioning
confidence: 54%
“…Median/mean MPRs have been reported in other studies in the range of 0.64 and 0.96. 9,11,19,20 Thirty-one percent of patients in our study were found to have a MPR < 0.9. Past studies have reported 30% to 46% of patients to be non-adherent to their TKI regimen.…”
Section: Discussionmentioning
confidence: 54%
“…This is of concern as medication non-adherence negatively impacts on multiple health-related outcomes, including treatment effectiveness, [11][12][13][14][15][16][17][18] health care costs [19,20] and health care utilisation. [9,13,19]…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients included in each study ranged from 19 [11] to 2,145 [57] with a mean number of 292 patients. There was wide variation in the methods used to assess medication adherence, ranging from patient self-report (n=17; 33%) [5,6,9,10,31,34,37,44,45,51,60,61,[64][65][66][67][68], claims data (n = 12; 23%) [13,14,32,36,38,39,41,49,50,[54][55][56], Medication Event Monitoring Systems (MEMS) (n=7; 13%) [4,8,29,42,43,47,59]; chart review (n=6; 12%) [11,40,44,61,65,68] and pill counts (n = 4; 7.7%) [5,30,48,…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 It has been demonstrated by several prospective and retrospective studies that overall survival or recurrence-free survival of CML patients depend on continuous and daily IM oral administration. 49 However, poor adherence to this medication has remained a challenge, due to the false feeling of healing, especially in low educational attainment patients living in developing countries. 10 Inefficient adherence to the CML treatment generates drastic consequences on individual and public health, increasing morbidity/mortality and costs of treatment, including therapeutic failure, drug resistance, relapse, and disease progression.…”
Section: Introductionmentioning
confidence: 99%